2017
DOI: 10.1016/j.appet.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Associations between TV viewing at family meals and the emotional atmosphere of the meal, meal healthfulness, child dietary intake, and child weight status

Abstract: Background-Research on family meals has demonstrated that family meals are protective for many aspects of child and adolescent health. It is unclear whether distractions at family meals, such as watching TV, are associated with child weight and weight-related behaviors, the emotional atmosphere at the meal, or family meal healthfulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 40 publications
(80 reference statements)
0
30
1
4
Order By: Relevance
“…Besides, there is the role played by replacing meals at the family table with meals eaten in front of the TV. The family table meal is associated with higher consumption of fruits and vegetables as well as lower intake of sugary beverages by children (Christian, Evans, Hancock, Nykjaer, & Cade, ; Fink, Racine, Mueffelmann, Dean, & Herman‐Smith, ), whereas eating in front of a TV is associated with lower overall quality of children's diet (Trofholz, Tate, Miner, & Berge, ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there is the role played by replacing meals at the family table with meals eaten in front of the TV. The family table meal is associated with higher consumption of fruits and vegetables as well as lower intake of sugary beverages by children (Christian, Evans, Hancock, Nykjaer, & Cade, ; Fink, Racine, Mueffelmann, Dean, & Herman‐Smith, ), whereas eating in front of a TV is associated with lower overall quality of children's diet (Trofholz, Tate, Miner, & Berge, ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose the reference category of no TV exposure given that research has indicated that both background TV and TV engagement may have negative effects on child health. 11 As such, we were interested in whether these two separate TV use variables were predicted by early childhood factors.…”
Section: Methodsmentioning
confidence: 99%
“…Possible mechanisms include exposure to obesogenic food advertising (which can have both immediate effects on dietary intake, and longer term effects on fast food preferences [11,12]); adverse effects of mealtime screen use on appetite regulation and control [13]; and less parental monitoring of food consumption [14]. The social and physical context of mealtimes may have independent and/or interactive effects on children's diet, although it is not clear whether mealtime screen use compromises or promotes a positive atmosphere [15,16].…”
Section: Family Mealtime Environmentmentioning
confidence: 99%